Nafion membrane channel structure studied by small-angle X-ray scattering and Monte Carlo simulations - Fernandez Bordin, Santiago Pablo (2018)
The structure of Nafion 117 membranes was studied through SAXS experiments and 2D pattern simulations. Measurements were taken for different moisture conditions by synchrotron radiation, and for different temperatures through X-ray tube irradiation. The experimental profiles were fitted through simulations based on a new structural model including: the amorphous polymer matrix, polymer crystallites, and inverse core-shell type channels conformed by water cylinders and sulfonic chains. The geometrical parameters intervening in the simulation of the SAXS patterns were optimized for each experimental condition. This approach allowed the proper description of the experimental SAXS profiles for the various moisture conditions studied. In addition, a recent lamelar model was also included in the assessments, and the corresponding performances were discussed.